Education À L’entrepreneuriat Et Propension À Entreprendre En Contexte De Formation Professionnelle En Côte d’Ivoire - Hillarion, Benie; Yeo, Soungari (European Scientific Journal, ESJ, 2017)
Entrepreneurship education was introduced as a formal discipline in vocational training programs in the late 1990s. This study reflects on the relevance of this education to entrepreneurship in terms of the persistence of unemployment and the underemployment of graduates. Its general objective is to analyze the influence of the satisfaction of the training expectations of the trainees on their propensity to undertake. The survey was carried out at the Yopougon Business Professional High School and the Riviera Professional Hotel School. The instrument used to capture the level of satisfaction of trainees’ expectations and their entrepreneurial propensity is a questionnaire with scales of measurement with three categories of response. The results establish a growing monotonous relationship between the satisfaction of the trainees expectations and their propensity to undertake. These results also indicate that satisfying three of the expectations expressed by trainees has a significant influence on their propensity to undertake. Entrepreneurship education is an effective strategy for the social construction of vocational integration through entrepreneurship among trainees in vocational training.